Design of polymer based directional coupler thermooptic optical switch - Abu Sahmah Mohd. Supa'at; Abu Bakar Mohammad, 1959-; Norazan Mohd. Kassim; International Conference on Electrical and Computer Engineering (3rd : 2004 : Dhaka, Bangladesh) (Skudai : Universiti Teknologi Malaysia, 2004)
40